2011
DOI: 10.1158/1541-7786.mcr-10-0372
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with Fibroblasts Are Distinct in Basal-Like and Luminal Breast Cancers

Abstract: Basal-like breast cancers have several well-characterized distinguishing molecular features, but most of these are features of the cancer cells themselves. The unique stromal-epithelial interactions, and more generally, microenvironmental features of basal-like breast cancers have not been well characterized. To identify characteristic microenvironment features of basal-like breast cancer, we performed cocultures of several basal-like breast cancer cell lines with fibroblasts and compared these with cocultures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 53 publications
8
116
0
Order By: Relevance
“…miR-520/373 family directly targets TGFBR2 and their expression inversely correlates in ER À primary breast cancer samples As the pro-inflammatory cytokines IL-6 and IL-8 had previously been reported to modulate cell motility in breast cancer (Wu et al, 2008;Walter et al, 2009;Camp et al, 2011), and NF-kB inhibition in ER À breast cancer cells had been previously reported to abrogate metastasis formation (Park et al, 2007), we hypothesized that miR-373 and miR-520c might have an inhibitory role in cell invasion through deregulation of NF-kB signaling. To investigate this hypothesis, we used the highly invasive and ER À breast carcinoma cell line MDA-MB-231.…”
Section: Resultsmentioning
confidence: 99%
“…miR-520/373 family directly targets TGFBR2 and their expression inversely correlates in ER À primary breast cancer samples As the pro-inflammatory cytokines IL-6 and IL-8 had previously been reported to modulate cell motility in breast cancer (Wu et al, 2008;Walter et al, 2009;Camp et al, 2011), and NF-kB inhibition in ER À breast cancer cells had been previously reported to abrogate metastasis formation (Park et al, 2007), we hypothesized that miR-373 and miR-520c might have an inhibitory role in cell invasion through deregulation of NF-kB signaling. To investigate this hypothesis, we used the highly invasive and ER À breast carcinoma cell line MDA-MB-231.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction mammoplasty fibroblast (RMF-GFP) is a stable cell line that constitutively expresses GFP (62). RMF-GFPs were maintained as previously published (28) in RPMI medium. GFP expression was obtained through a lentiviral infection with puromycin as the selection antibiotic.…”
Section: Methodsmentioning
confidence: 99%
“…We then perform GNR diffusion imaging in two biological models where pathology is strongly linked to mechanical properties. The first is an in vitro ECM model of the human mammary stroma, in which the mechanical microenvironment may modulate breast cancer aggressiveness (28,29). The second is that of actively transporting pulmonary mucus, in which the viscoelastic properties of the mucus are modified in diseases such as chronic obstructive pulmonary disease and cystic fibrosis, leading to loss of mucociliary transport and chronic infection (30,31).…”
mentioning
confidence: 99%
“…Fresh tissues from invasive tumors, non-neoplastic adjacent breast tissue and mammary fat tissue were collected at the time of breast surgery and snap frozen in liquid nitrogen. Based on in vitro evidence that basal-like and luminal tumors are associated with distinctive microenvironments (20), we oversampled these subtypes. All of the participants provided written informed consent under a protocol approved by the U.S. National Cancer Institute and local (Polish) institutional review boards.…”
Section: Methodsmentioning
confidence: 99%